USING VIDEO MATERIALS - To‘raqulova Sobira; Toshmirzayeva Sitora; Sattorova Sabohat (TADQIQOTLAR, 2025)
Annotation This  paper  examines  the  purposeful  application  of  video  content  in  teaching English to intermediate (B1) learners, focusing on its instructional benefits, classroom implementation techniques, and real-life usage. It outlines how video enhances learner involvement,  promotes  better  contextual  and  cultural  understanding,  and  boosts listening  abilities.  The  article  also  presents  educators  with  practical  methods  for selecting suitable videos, creating engaging tasks, and sustaining student motivation. Aimed at English teachers, this resource supports the integration of multimedia tools to develop communication skills and learner independence.